Examination of the role of necroptotic damage-associated molecular patterns in tissue fibrosis - Liu, Xu; Lu, Feng; Chen, Xihang (Frontiers in Immunology, 2022)
Fibrosis is defined as the abnormal and excessive deposition of extracellular matrix (ECM) components, which leads to tissue or organ dysfunction and failure. However, the pathological mechanisms underlying fibrosis remain unclear. The inflammatory response induced by tissue injury is closely associated with tissue fibrosis. Recently, an increasing number of studies have linked necroptosis to inflammation and fibrosis. Necroptosis is a type of preprogrammed death caused by death receptors, interferons, Toll-like receptors, intracellular RNA and DNA sensors, and other mediators. These activate receptor-interacting protein kinase (RIPK) 1, which recruits and phosphorylates RIPK3. RIPK3 then phosphorylates a mixed lineage kinase domain-like protein and causes its oligomerization, leading to rapid plasma membrane permeabilization, the release of cellular contents, and exposure of damage-associated molecular patterns (DAMPs). DAMPs, as inflammatory mediators, are involved in the loss of balance between extensive inflammation and tissue regeneration, leading to remodeling, the hallmark of fibrosis. In this review, we discuss the role of necroptotic DAMPs in tissue fibrosis and highlight the inflammatory responses induced by DAMPs in tissue ECM remodeling. By summarizing the existing literature on this topic, we underscore the gaps in the current research, providing a framework for future investigations into the relationship among necroptosis, DAMPs, and fibrosis, as well as a reference for later transformation into clinical treatment.